2022
DOI: 10.1021/acs.nanolett.1c03833
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Anisotropic Waveguide Exciton Polaritons in Tin Sulfide

Abstract: In recent years, novel materials supporting in-plane anisotropic polaritons have attracted a great deal of research interest due to their capability of shaping nanoscale field distributions and controlling nanophotonic energy flows. Here we report a nano-optical imaging study of waveguide exciton polaritons (EPs) in tin sulfide (SnS) in the near-infrared (near-IR) region using scattering-type scanning near-field optical microscopy (s-SNOM). With s-SNOM, we mapped in real space the propagative EPs in SnS, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…By tuning the laser energy, we found that the fringe pattern demonstrates a systematic variation. As introduced in previous studies, 20–22,28–30 such fringes are generated due to the interference between tip-backscattered photons [labeled as “P1” in Fig. 1a] and beam paths involving propagative in-plane modes.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…By tuning the laser energy, we found that the fringe pattern demonstrates a systematic variation. As introduced in previous studies, 20–22,28–30 such fringes are generated due to the interference between tip-backscattered photons [labeled as “P1” in Fig. 1a] and beam paths involving propagative in-plane modes.…”
Section: Resultsmentioning
confidence: 98%
“…Based on the interference mechanism involving beam paths ‘P1’ and ‘P2’ (Fig. 1a), we can establish a direct relationship between the fringe period ( ρ ) and the wavelength of the in-plane mode ( λ p ): 20–22 1/ ρ = 1/ λ p − cos α / λ 0 ,where λ 0 is the free-space photon wavelength and α is the incident angle of the laser beam ( α ≈ 30°) [see Fig. 1a].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Luan et al reported the real-time observation of an anisotropic exciton−polariton in an SnS waveguide. 31 Maragkakis et al demonstrated polarizationresolved second harmonic generation imaging of in-plane anisotropy in a layered SnS crystal. 32 Alberding et al investigated the ultrafast optical response of a nano-to micrometer-sized SnS film with transient terahertz spectroscopy, in which the carrier mobility and carrier dynamics of the thin films exhibit the strong particle size dependence.…”
mentioning
confidence: 99%
“…The investigation of the dynamical anisotropic response of SnS following photoexcitation is of great interest for understanding the originality of the anisotropy, expanding its possible application in polarization-sensitive photodetectors, and offering a new degree of freedom for manipulating the electronic, optoelectronic, and optical properties in a non-equilibrium state. Recently, Luan et al reported the real-time observation of an anisotropic exciton–polariton in an SnS waveguide . Maragkakis et al demonstrated polarization-resolved second harmonic generation imaging of in-plane anisotropy in a layered SnS crystal .…”
mentioning
confidence: 99%